Nuclear Structure for 24Mg within sd-Shell Model Space Hamiltonians - Anwer A. Al-Sammarraie; F. I. Sharrad; Hasan Abu Kassim
In this study, we assess the accuracy of the sd- shell Hamiltonians CW, USD, USDA and USDB in calculating the excited states in 24Mg nucleus on the basis of recently reported experimental results. The assessments rely on the calculations of the energy levels, reduced electric quadrupole transition probabilities, and reduced magnetic dipole transition probabilities. We show a comparison between the four Hamiltonians calculations and demonstrate the possibility of confirming known states and suggesting new states.
Keywords: Physics; Nuclear physics